Contaminación electromagnética: medición de RNI - Aldasoro, Roberto (2012)
The electromagnetic density of the atmosphere has increased in recent years due to the major technological development, generating a new kind of pollution, which some authors called "electromagnetic pollution". The use of electromagnetic systems that generate non-ionizing radiation (NIR) involves a risk, unknown, which is framed within acceptable risks, and that it is necessary to quantify. The UNITEC LEMA Lab, dedicated to environmental education, echoing this concern to the growing proliferation of aerials of cellular telephony and few studies of this matter, has begun to perform periodic measurements on sites agreed with the operators of cellular telephony and alternative sites considered critics, creating a database with measurements repeatable for further processing and comparison making use of latest technology equipment. From this activity, UNITEC LEMA has begun the education and guidance of professionals and students of engineering that will develop its activities in the field of telecommunications, to assure the responsibility to the University with the society. This paper presents the first results of the measurements carried out in the city of Comodoro Rivadavia, and an overview of measurements carried out in the cities of Mendoza and Neuquén and the municipalities of Almirante Brown, San Martín and the Autonomous City of Buenos Aires. Also includes a brief reference to the current regulatory framework. Measurements were made according to the regulations and the results obtained were in the range within the reference limit values fixed according to the rules, of which the most restrictive is located in 0.2 mW/cm2 power density.